ANALISIS PENERAPAN GOOD GOVERNANCE BISNIS SYARIAH DALAM MENCAPAI MAQASHID SYARIAH PADA BANK UMUM SYARIAH DI INDONESIA - Herlyanto, Fredy Dwi (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2020)
This study aims to analyze the application of good governance business sharia in achieving maqashid sharia in Islamic sharia banks in Indonesia. To analyze the application of sharia business governance, namely by using content analysis that refers to the national governance policy committee as many as 47 indicators. To analyze the achievement of maqashid sharia using financial ratios that reflect the three components of maqashid sharia, namely education, justice, and benefit. The results of this study, namely the application of sharia business governance in the amount of 93% has not had an impact on the achievement of overall sharia maqashid during 2015-2017. If viewed based on each goal, the implementation of sharia business governance will have an impact on achieving creating justice.Â